2006
DOI: 10.1016/j.ijnurstu.2005.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Social regulation, medicalisation and the nurse's role: Insights from an analysis of nursing documentation

Abstract: Background: Medicine is recognized as a dominant source of governmentality and social regulation, and although nursing has been implicated in the same process, analytical work in this area has been sparse. Objectives: The article aims to present an analysis of nursing records in order to understand the structural and social processes that mediate the texts. Methods: 45 sets of nursing records drawn from four clinical sites in Ireland were subjected to a discourse analysis. Results: This article focuses on two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 10 publications
0
37
0
1
Order By: Relevance
“…The abuse reported by both patients and nurses seemed to be clearly related to issues of power and control, hierarchy and order. Within hospitals throughout the developed and developing world, the dominant discourse regarding childbirth is a medical discourse (Hyde et al, 2006;KabakianKhasholian et al, 2000;Weaver, 2000). While the medical discourse, like most discourses, is not a monolithic discourse, but itself an outcome of specific historical developments in particular contexts (Treichler, 1990), it can be said that within all medical discourses the ideal childbirth is one that is ordered, surveillant, technocratic and risk-averse (Adams, 1994;Cosslett, 1994;Davis-Floyd, 1994;El-Nemer, Downe & Small, 2006;Kruger, 2006;Marshall & Woollett, 2000;Treichler, 1990;Wall, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The abuse reported by both patients and nurses seemed to be clearly related to issues of power and control, hierarchy and order. Within hospitals throughout the developed and developing world, the dominant discourse regarding childbirth is a medical discourse (Hyde et al, 2006;KabakianKhasholian et al, 2000;Weaver, 2000). While the medical discourse, like most discourses, is not a monolithic discourse, but itself an outcome of specific historical developments in particular contexts (Treichler, 1990), it can be said that within all medical discourses the ideal childbirth is one that is ordered, surveillant, technocratic and risk-averse (Adams, 1994;Cosslett, 1994;Davis-Floyd, 1994;El-Nemer, Downe & Small, 2006;Kruger, 2006;Marshall & Woollett, 2000;Treichler, 1990;Wall, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Various studies show that WMSDs are common among healthcare workers [28][29][30]. Nuikka et al [31] showed that workload in primary care situations and in transporting the patient can be classified as moderately heavy, based on heart rate and relative workload.…”
Section: Temporal Aspect Of Job Demandmentioning
confidence: 99%
“…Many medical terminologies were borrowed in the development of nursing [49,50] . For this reason, nurses would have possessed prior knowledge in the context of nursing which was external to the online conference.…”
Section: Discussionmentioning
confidence: 99%
“…Also, these diagnoses and the subsequent nursing treatment plans were based on nurses' unique knowledge to guide nursing practice. Yet, the contents were communicated to non-nursing healthcare professionals for actions [50] . In this regard, nursing documentation as an important source of social regulation of patients' activities of daily living was also a critically dominant source of governmentality [51] which targeted not only nurses, but also all other allied health professionals [50] .…”
Section: Nurses' Text Resembling Nursing Documentation By Which Powermentioning
confidence: 99%
See 1 more Smart Citation